2010
DOI: 10.1111/j.1939-165x.2010.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of blood cells in the Leopard Cat (Prionailurus bengalensis)

Abstract: These findings will facilitate interpretation of hematologic results for future investigative and diagnostic studies of this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
(25 reference statements)
2
6
0
Order By: Relevance
“…The heterogeneity of basophil granules seen with TEM was similar to that found in other raptors such as Blyth's hawk eagle, the crested serpent eagle, the shikra, and the roadside hawk, Buteo magnirostris . Light microscopic observations of lymphocyte and monocyte morphology and ultrastructure were similar to those of other avian and mammalian species, showing similar forms across the orders …”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The heterogeneity of basophil granules seen with TEM was similar to that found in other raptors such as Blyth's hawk eagle, the crested serpent eagle, the shikra, and the roadside hawk, Buteo magnirostris . Light microscopic observations of lymphocyte and monocyte morphology and ultrastructure were similar to those of other avian and mammalian species, showing similar forms across the orders …”
Section: Discussionsupporting
confidence: 54%
“…Only BG reactions were positive in basophils from the three kite species, which is similar to those from the crested serpent eagle and shikra . ANAE, a nonspecific esterase enzyme for the monocytic lineage in mammals, felids,and reptiles, showed no reactivity in monocytes in these three kite species. The ANAE‐positivity of lymphocytes was similar to other reported findings for birds, reptiles, and mammals .…”
Section: Discussionmentioning
confidence: 64%
“…Basal level of RBC in far‐east wild cats was higher than in most cat species (Caro et al., ; Kocan et al., ; Prihirunkit et al., ; Salakij, Prihirunkit, Narkkong, Apibal, & Tongthainun, ), but very similar to leopard cat ( P. bengalensis ), which was physically immobilized also without anesthesia within an hour (Salakij et al., ). We showed that RBC number decreased in 20 min after the beginning of capture procedure.…”
Section: Discussionmentioning
confidence: 73%
“…During the last 30 years, the use of blood profiles to estimate the welfare of wild cats in both captive and wild settings has become a usual practice among zoo veterinaries and field zoologists. At present, for 17 of the 38 wild cat species blood profiles have been obtained and described in scientific literature (Akuzawa, Mochizuki, & Yasuda, ; Brown, Lappin, Brown, Munkhtsog, & Swanson, ; Caro et al., ; Dunbar, Nol, & Linda, ; Erasmus, ; Kocan, Blouin, & Glenn, ; Marco, Martinez, Pastor, & Lavin, ; Prihirunkit, Salakij, Apibal, & Narkkong, ; Salakij, Salakij, Narkkong, Sirinarumitr, & Pattanarangsan, ,b, b, , , and others). However, blood profiles can be influenced significantly by the sampling procedure, including capture method, type of anesthesia, and time to blood collection (Moen, Rasmussen, Burdett, & Pelican, ; Serieys et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation